WED 014 Oct minimises unnecessary investigation for suspected papilloedema - Thomas, Coysh; David, Whiteside; Sarah, Williamson; Louwai, Muhammed; Vinod, Metta; Fatemeh, Geranmayeh; Barry, Seemungal; Carolyn, Gabriel; Joanna, Ball; Richard, Nicholas (Journal of neurology, neurosurgery and psychiatry, 2018)
BackgroundOptical coherence tomography (OCT) is a rapid and painless way to provide a record of the optic disc structure. Though not specific, it can identify swollen optic discs. We determined the impact of OCT prior to referral on the pathway for managing suspected papilloedema.MethodsAudit of adults referred from the Western Eye Hospital to St Mary’s Hospital with suspected papilloedema was performed between 1/1/17 and 16/5/17. A follow-up re-audit was performed from 1/6/17 to 31/8/17 following implementation of OCT prior to referral.ResultsThe initial audit identified 50 patients over 136 days and the re-audit 26 patients over 92 days. In the initial audit 6/50 had OCT and 17/50 (34%) were admitted. 6/50 patients were subsequently found not to have papilloedema on fundoscopy, none of whom had OCT. 4/6 underwent unnecessary neuroimaging and lumbar puncture. 3 were admitted, equating to 18% of all admissions, for an average of 2.3 days. In the re-audit all had OCT, 6/26 (23%) were admitted and none were subsequently found not to have papilloedema.ConclusionUse of OCT prior to referral for suspected papilloedema helps to reduce unnecessary investigations.